2016
DOI: 10.1001/jama.2016.12126
|View full text |Cite
|
Sign up to set email alerts
|

Association Between MRI Exposure During Pregnancy and Fetal and Childhood Outcomes

Abstract: IMPORTANCE Fetal safety of magnetic resonance imaging (MRI) during the first trimester of pregnancy or with gadolinium enhancement at any time of pregnancy is unknown. OBJECTIVE To evaluate the long-term safety after exposure to MRI in the first trimester of pregnancy or to gadolinium at any time during pregnancy. DESIGN, SETTING, AND PARTICIPANTS Universal health care databases in the province of Ontario, Canada, were used to identify all births of more than 20 weeks, from 2003-2015. EXPOSURES Magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
358
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 647 publications
(406 citation statements)
references
References 32 publications
(35 reference statements)
3
358
0
14
Order By: Relevance
“…Such reagents are not typically administered to pregnant women due to potential risks to the fetus 48,49 . Recently, we demonstrated that T 2 * based MRI measurements can also be used to characterize the entire placenta at the level of individual spiral artery perfusion domains.…”
Section: Commentmentioning
confidence: 99%
“…Such reagents are not typically administered to pregnant women due to potential risks to the fetus 48,49 . Recently, we demonstrated that T 2 * based MRI measurements can also be used to characterize the entire placenta at the level of individual spiral artery perfusion domains.…”
Section: Commentmentioning
confidence: 99%
“…Gadolinium administration is contraindicated in pregnancy due to higher risk of adverse birth outcomes, such as stillbirth, neonatal death and a broad set of rheumatological, inflammatory or infiltrative skin conditions 9. In addition, there is growing evidence about dose-dependent neuronal gadolinium accumulation in the general population 10.…”
Section: Discussionmentioning
confidence: 99%
“…MRI of the breasts during pregnancy is not the preferred method, as gadolinium is contraindicated. Fetal gadolinium exposure is associated with rheumatologic, inflammatory, or infiltrative skin conditions, stillbirth, and neonatal death 19. Iodinated contrast may cause neonatal thyroid dysfunction.…”
Section: Methodsmentioning
confidence: 99%